(untitled) (Journal of the Association for the Study of Australian Literature, 2009)
In debates about appreciation and interpretation of Literature, Christopher Koch is an outspoken, and often controversial, figure. He deplores what he terms the postmodern approach to critical analysis, questioning why children are ‘studying films, comic strips and hopelessly bad contemporary novels with social messages, rather than major works that have stood the test of time’. It is somewhat surprising then, to study Koch’s novels and uncover how frequently his work is informed by childhood influences and his love of comic books. This essay considers whether unwittingly Koch, as an author, is an instrument of social forces.